Development and Evaluation of an Integrated Digital Patient Platform During Oncology Treatment. (February 2020) - De Regge, Melissa; Decoene, Elsie; Eeckloo, Kristof; Van Hecke, Ann
Background: Patient platforms are seen as promising technologies in an integrated care approach to involve cancer patients in their own health care and to support them in managing their personal health information. However, few digital platforms have been codesigned with patients and caregivers. Objective: To develop, implement, and evaluate the feasibility and applicability of a digital oncology platform (DOP) for patients with cancer. Method: A mixed-method study was used, employing a survey, interviews, and logged data from caregivers and patients. The DOP was designed in cooperation with Information Technology (IT) staff, caregivers, and patients. Results: The DOP was actively used by half of the patients. These active patients were positive about the DOP. Caregivers acknowledged the added value but also indicate that additional workload was involved. Oncology nurse specialists are the users of the platform. General practitioners have indicated their interest in the platform. Conclusion: Thanks to the codesign process, the DOP could be tailored to the expectations of the end users. This study provides insight into which DOP functionalities the patients were interested in and includes further recommendations for implementation.